Equação de Fokker-Planck para o cálculo da probabilidade de infiltração por água: aplicação ao repositório de Abadia-Goiás - Gabcan, Ludmila (2019)
The research developed can be classified as a nuclear safety analysis problem inserted in the field of risk management of radioactive waste. The simple and efficient modeling was constructed with the objective of developing the Fokker-Planck Eq. for the calculation of the reliability attributes required for risk-informed decision-making, involved in the analysis of water infiltration inside the repository located in Abadia - Goiás. The solution of the Fokker-Planck Equation was obtained analytically through the Trotter method, producing as results probability data associated with the increase of probability the column of liquid infiltrated by water. The modeling was unidimensional, and the calculations were performed for the geometric center of the repository crypt, place of greater sensitivity of occurrence of accidental scenarios, thus being able to be extended to the other places in the crypt, without loss of generality. The results attributed the highest chances of occurrence to 0.80m of infiltrated liquid height, a fraction of the crypt height that corresponds to less than 19% of its total internal height. Such data add elements height such that can be used by experts on the problem of risk scenarios related to the disposal of radioactive waste.